Ethical Issues in Behavioral Neuroscience - Lee, Grace; Illes, Judy; Ohl, Frauke (Current Topics in Behavioral Neurosciences,, 2015)
Behavioral neuroscience encompasses the disciplines of neurobiology and psychology to study mechanisms of behavior. This volume provides a contemporary overview of the current state of how ethics informs behavioral neuroscience research. There is dual emphasis on ethical challenges in experimental animal approaches and in clinical and nonclinical research involving human participants.